Чапаев сярысь веросъёс: [пиналъёслы] / А. Т. Кононов - Кононов Александр Терентьевич (Удмуртгосиздат, 1952)
Экземпляры: КР (20020330) / Инвентарный номер: у7027 / Сис.шифр: Р2 / Авт.знак: К 64 / ГРНТИ: 17.82 / ББК: 84(2)